2015
DOI: 10.3109/14767058.2015.1020293
|View full text |Cite
|
Sign up to set email alerts
|

A new anti-microbial combination prolongs the latency period, reduces acute histologic chorioamnionitis as well as funisitis, and improves neonatal outcomes in preterm PROM

Abstract: Objective Antibiotic administration is a standard practice in preterm premature rupture of membranes (PROM). Specific antimicrobial agents often include ampicillin and/or erythromycin. Anaerobes and genital mycoplasmas are frequently involved in preterm PROM, but are not adequately covered by antibiotics routinely used in clinical practice. Our objective was to compare the outcomes of PROM treated with standard antibiotic administration versus a new combination more effective against these bacteria. Study De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 231 publications
0
69
0
4
Order By: Relevance
“…66,67 A recent study, however, examined treatment with an antibiotic regimen of ceftriaxone, clarithromycin, and metro-nidazole, which the authors found reduced histologic chorioamnionitis and funisitis. 68 Therefore, further investigation is necessary to understand how antibiotics may or may not alter the placental membrane microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…66,67 A recent study, however, examined treatment with an antibiotic regimen of ceftriaxone, clarithromycin, and metro-nidazole, which the authors found reduced histologic chorioamnionitis and funisitis. 68 Therefore, further investigation is necessary to understand how antibiotics may or may not alter the placental membrane microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…This antibiotic combination was also associated with a more successful eradication of intra-amniotic inflammation/infection and prevented secondary intraamniotic inflammation/infection more frequently than an antibiotic regimen which included ampicillin and/or cephalosporins in patients with PPROM [108].…”
Section: Antibiotics and Probioticsmentioning
confidence: 96%
“…Lee et al found that the combination of ceftriaxone, clarithromycin and metronidazole prolonged the latency period, reduced acute histologic chorioamnionitis/funisitis, and improved neonatal outcomes in patients with PPROM, especially with a intra-amniotic infection/ inflammation assessing by positive amniotic fluid culture and/or an elevated amniotic fluid MMP-8 concentration (>23 ng/mL) [107,108]. This antibiotic combination was also associated with a more successful eradication of intra-amniotic inflammation/infection and prevented secondary intraamniotic inflammation/infection more frequently than an antibiotic regimen which included ampicillin and/or cephalosporins in patients with PPROM [108].…”
Section: Antibiotics and Probioticsmentioning
confidence: 99%
“…Biofilms are also more common in infections associated with a device (e.g., intra-uterine contraceptive device, prosthetic valves, catheters). Notably, the eradication of intra-amniotic infection diagnosed by amniocentesis in patients with preterm prelabor rupture of membranes (PROM) 184, 185 and those with an asymptomatic short cervix 137 is possible with the administration of intravenous antibiotics to the mother. Success has been documented by demonstrating the absence of microorganisms at the time of a second amniocentesis 137, 184 .…”
Section: Pathways Of Microbial Invasion Of the Amniotic Cavitymentioning
confidence: 99%